مصطلح "التردد" عند الشيخ خليل دراسة في كتاب مواهب الجليل - منصور عسول; مختار زيغم ي; د/نعيم ي زيغم ي (جامعة عمار ثليجي الاغواط, 2023)
لْخص الب ثٌ: الحمد والصلاة والسلا م عل رسول خ أما عد: ذ ا ح متواض في الفقه المقارن داقل المذ ب المال ي، أو ما عرف الخلاف النازل ويتعلع حثن ا ذا إمامي جليلي م أئمة المذ ب المال ي و ما الشيم قليل رحمه خ اولإمام الحلاب رحمه خ، وتتمثل علاقتهما بهذا البح في أننا ندر مصللح ا للشيم قليل جكرو في مختصرو المشهور و و مصللح "التردد" الذ خ قصد ه تردد المتبقري في النقل ع المتقدمي أو تردد م لعدم ن ص المتقدمي . ودرسنا ذا المصللح ع طريع شر الإمام الحلا ب لمختصر الشيم قليل المسم "موا ب الجليل في شر مختصر قليل" واقتصر نا في د ا رستنا عل نماج، م كتاب اللهارة وكتاب الصلاة . ولقد رتبنا ذا البح ترتيبا كما يلي : مقدمة، و فصلي ، الفصل الأول جعلناو للت ا رجم وال تب ، اولفصل الثاني جكرنا فيه د ا رسة مصللح التردد وعلاقته الخلاف النازل، اولمواض التي جكر فيها الشيم قليل مصللح التردد في كتاب اللهارة وكتاب الصلاة، ث م جعلنا قاتمة للبح جكرنا فيها أ م النتائج وبع ا لاقت ا رحا . و ذا و ملخ ص حثنا المتواض وقير الختا م الصلاة والسلام عل قير الأنام سيدنا محمد صلى الله عليه وسلم . 106 Research SummaryResearch Summary Research Summary Research SummaryResearch SummaryResearch SummaryResearch SummaryResearch SummaryResearch SummaryResearch SummaryResearch Summary Praise be to Allah and peace and blessings be upon the Messenger of Allah But after: This is a modest research in comparative jurisprudence within the Maliki school, or what is known as the dispute descending and our research relates to this two great imams of the Maliki school of thought, namely Sheikh Khalil, may God have mercy on him and Imam Al-Hattab, may God have mercy on him, and their relationship to this research is that we are studying a term for Sheikh Khalil mentioned in his famous abbreviation, which is the term "hesitation", which is intended by the reluctance of the latecomers to transfer from the applicants or their hesitation for not writing the applicants We studied this term through Imam al-Hattab's explanation of Sheikh Khalil's summary called "The Talents of Galilee in the Explanation of Khalil's Mukhtasar" and we limited our study to samples from the Book of Purity and the Book of Prayer. We have arranged this research in a systematic order as follows: Introduction in which we mentioned the importance and objectives of this study and raised the problem of the research and the plan followed in it. Then we divided this research into two chapters: The first chapter we made it for translations and books was from two sections: The first chapter we made for translations and books, it was from two sections: the first section is a translation of Sheikh Khalil and a definition of his book "Al-Mukhtasar", and the second section is a translation of Imam Al-Hattab and a definition of his book "The talents of Galilee in a brief explanation of Khalil" Chapter II also divided it into two sections: The first section is a study of the term frequency and its relationship to the descending dispute, and the second section is specific to the places where Sheikh Khalil mentioned the term hesitation in the Book of Purity and the Book of Prayer and we made these places in the form of issues in which we mention the explanation of Imam Al-Hattab and his comments and edit them The subject of dispute and we mention the statements of the scholars and their preferences. Then we made a conclusion to the research in which we mentioned the most important results and some suggestions. 107 This is the summary of our humble research and the best conclusion peace and blessings are upon the best of people, our master Muhammad, may God bless him and grant him peace.